Ni(II) Complex Extended Structures Sustained by Hydrogen Bonding, p-p and C-H···p Interactions - Zhang, Zhen-Ming; Yin, Fu-Jun; Zhao, Gui; Wang, Li-Ping; Zhao, Hong (Asian Journal of Chemistry, 2014)
The complex [Ni(NAA)2(im)6](1) (where H2NAA = a-naphthylacetic acid and im = imidazole) has been synthesized under solvothermal conditions. The complex fully characterized by IR spectroscopy, elemental analysis and single crystal X-ray diffraction. In complex 1, Ni(II) is coordinated by six N atoms with a octahedral coordination geometry. This mononuclear complex is further extended into three-dimensional structure via p-p, C-H···p and hydrogen bonding interactions. The thermal stable property of complex 1 is also reported.